2021
DOI: 10.1080/02656736.2021.1922763
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between radiofrequency ablation combined with mifepristone and radiofrequency ablation for large uterine fibroids

Abstract: Objective: To evaluate the clinical outcomes of transvaginal ultrasound-guided (US-guided) radiofrequency ablation (RFA) combined with mifepristone for the treatment of large uterine fibroids. Methods: Between June 2016 and December 2018, a total of 30 patients with symptomatic uterine fibroids (!5cm) who underwent transvaginal US-guided RFA combined with mifepristone were included in this retrospective study. A matching cohort of 30 patients underwent transvaginal USguided RFA without mifepristone as controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A rat experiment showed that the role of Mif in drug abortion may be related to increase in expression levels of Malondialdehyde (MDA), activated caspase 3, caspase 9 and recombinant B-cell lymphoma 2 (Bcl-2)-associated X protein (BAX), as well as the down-regulation of Superoxide Dismutase (SOD) and Bcl-2 [13] . Besides, compared with RFA intervention alone, Mif combined with ultrasoundguided Radiofrequency Ablation (RFA) for large UFs has been indicated to not only significantly reduce the mean ablation time and mean number of punctures, but also improve the average resolution rate of UFs, the quality of life and symptom scores without causing major complications, suggesting that Mif also has certain therapeutic potential in large UFs [14] . The dosage of Mif in the treatment of UFs is still controversial.…”
Section: Mifepristonementioning
confidence: 99%
“…A rat experiment showed that the role of Mif in drug abortion may be related to increase in expression levels of Malondialdehyde (MDA), activated caspase 3, caspase 9 and recombinant B-cell lymphoma 2 (Bcl-2)-associated X protein (BAX), as well as the down-regulation of Superoxide Dismutase (SOD) and Bcl-2 [13] . Besides, compared with RFA intervention alone, Mif combined with ultrasoundguided Radiofrequency Ablation (RFA) for large UFs has been indicated to not only significantly reduce the mean ablation time and mean number of punctures, but also improve the average resolution rate of UFs, the quality of life and symptom scores without causing major complications, suggesting that Mif also has certain therapeutic potential in large UFs [14] . The dosage of Mif in the treatment of UFs is still controversial.…”
Section: Mifepristonementioning
confidence: 99%
“…Mifepristone, an anabolic steroid with antiprogesterone and antiglucocorticoid activity, is a commonly used SPRM. MFP is effective and well-tolerated in the treatment of UFs [ 19 , 21 , 22 ]. Multiple past studies have demonstrated that low-dose MFP maintains the same efficacy and has fewer adverse effects than high-dose MFP [ 20 , 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%